2016
DOI: 10.4103/2231-0762.178752
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dental neglect score on oral health among patients receiving fixed orthodontic treatment: A cross-sectional study

Abstract: Objective:Maintenance of meticulous oral health practices is critical for patients who are under orthodontic treatment as failure to do so can result in deterioration of periodontal health. Thus, the present study was commenced to assess dental negligence and oral health status among patients undergoing orthodontic treatment using dental neglect scale (DNS) questionnaire.Materials and Methods:The present cross-sectional study was planned and carried out among the 40 patients undergoing fixed orthodontic treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 11 publications
(16 reference statements)
0
23
0
1
Order By: Relevance
“…Thus, two-thirds of patients receiving orthodontic treatment brushed their teeth at least twice a day and for at least 2 min. Meanwhile, other studies showed a lower share of participants following the tooth brushing recommendations, and tooth brushing once a day was found to be prevalent among participants in Saudi Arabia [33] and India [34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, two-thirds of patients receiving orthodontic treatment brushed their teeth at least twice a day and for at least 2 min. Meanwhile, other studies showed a lower share of participants following the tooth brushing recommendations, and tooth brushing once a day was found to be prevalent among participants in Saudi Arabia [33] and India [34].…”
Section: Discussionmentioning
confidence: 99%
“…A regular usage of interproximal measures leads to higher action and maintenance of self-efficacy, a lower level of biofilm and better periodontal tissue status in orthodontic patients [45,46]. However, several studies revealed that the majority of patients were not familiar with a regular usage of interdental aids, such as dental floss or an interdental brush [34][35][36]43,[46][47][48]. This study suggested a reason for optimism, since 56% of participants receiving orthodontic treatment reported using interproximal measures, while significantly less non-orthodontic patients reported the same oral behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presence of fixed appliance intraorally is considered as a leading factor that causes hindrance for patients to properly clean their teeth [8]. This would cause a multitude of side effects mainly, periodontal problem.…”
Section: Discussionmentioning
confidence: 99%
“…A fim de driblar todos estes efeitos colaterais que atingem o periodonto do paciente em tratamento ortodôntico, muitos autores sugerem a realização da ortodontia em conjunto com uma manutenção periodontal, incluindo avaliações periodontais frequentes, controle de placa bacteriana e orientações de higiene bucal em todas as consultas (Alfuriji et al, 2014;Pandey et al, 2016;Cerroni et al, 2018).…”
Section: Tabulação E Análise Estatísticaunclassified